2020
DOI: 10.3389/fpls.2019.01778
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ATP Synthase c–Rings for Oxygenic Photosynthesis

Abstract: The conversion of sunlight into useable cellular energy occurs via the proton-coupled electron transfer reactions of photosynthesis. Light is absorbed by photosynthetic pigments and transferred to photochemical reaction centers to initiate electron and proton transfer reactions to store energy in a redox gradient and an electrochemical proton gradient (proton motive force, pmf), composed of a concentration gradient (DpH) and an electric field (Dy), which drives the synthesis of ATP through the thylakoid F o F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 111 publications
(157 reference statements)
0
19
0
Order By: Relevance
“…Instead of indirectly upregulating the production of ATP through upregulation of CET routes, it is conceivable to directly enhance chloroplast ATP synthase activity (Cardona et al, 2018; Davis and Kramer, 2020). The ATP synthase is composed of two rotary motor complexes (CF0/CF1) which are connected by two flexible stalks (Kühlbrandt, 2019).…”
Section: Improving Crop Yields Through Optimization Of Photosynthetic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of indirectly upregulating the production of ATP through upregulation of CET routes, it is conceivable to directly enhance chloroplast ATP synthase activity (Cardona et al, 2018; Davis and Kramer, 2020). The ATP synthase is composed of two rotary motor complexes (CF0/CF1) which are connected by two flexible stalks (Kühlbrandt, 2019).…”
Section: Improving Crop Yields Through Optimization Of Photosynthetic...mentioning
confidence: 99%
“…The ATP synthase is composed of two rotary motor complexes (CF0/CF1) which are connected by two flexible stalks (Kühlbrandt, 2019). The CF0 complex is embedded within the thylakoid membrane and consists of a ring of several c‐subunits, the numbers of which are organism/species‐dependent but remain constant under different conditions (between eight and 17 c‐subunits; Davis and Kramer, 2020). Each c‐subunit binds one proton from the thylakoid lumen, fueling the CF0 motor and subsequently the CF1 motor on the stromal side of the membrane, thus promoting the production of three ATP molecules per 360° rotation.…”
Section: Improving Crop Yields Through Optimization Of Photosynthetic...mentioning
confidence: 99%
“…For instance, the large c-ring in B. pseudomallei has a high ion-to-ATP ratio, making the enzyme an efficient ion pump and allowing the pathogen to deal with the hostile acidic host phagosome ( Schulz et al, 2017 ). The overwhelming majority of studies have demonstrated that c-ring stoichiometries within a given species do not vary with external conditions like medium pH, host membrane composition, or carbon source ( Meier and Dimroth, 2002 ; Meyer zu Tittingdorf et al, 2004 ; Meier et al, 2005b , 2007 ; Fritz et al, 2008 ; Davis and Kramer, 2020 ; but see also, e.g., Schemidt et al, 1998 ). However, genetically engineered rotors of modified size have been shown to function in both “directions” within their host cell—that is, edited F1–Fo complexes can both synthesize and hydrolyze ATP.…”
Section: If the Ring Fits: Variation In Rotor Size And Stoichiometrymentioning
confidence: 99%
“…In Gloeobacter violaceus, the ATP synthase stoichiometry may be related to the occurrence of all membrane-associated bioenergetic processes in the cell membrane. Davis & Kramer (2020) suggest that the higher number of c-subunits in ATP synthases in photosynthetic membranes than in respiratory membranes is related to the use of a large pH difference component of a PMF). This seems more plausible for thylakoid membranes, when the P (lumen) side of the membrane has a relatively unconstrained pH, at least compared to the P (periplasmic) side of the membrane plasma membrane of Gloeobacter.…”
Section: Synthesis Repair and Operation Of The Photosynthetic Apparatus Of Gloeobacter In Relation To Its Low-salinity Habitatmentioning
confidence: 99%